Plant Secondary Metabolite Transporters: Diversity, Functionality, and Their Modulation - Nogia, Panchsheela; Pati, Pratap Kumar (Frontiers in Plant Science, 2021)
Secondary metabolites play crucial roles in the vital functioning of plants such as growth, development, defense, and survival via their transportation and accumulation at the required site. However, unlike primary metabolites, the transport mechanisms of secondary metabolites are not yet well explored. There exists a huge gap between the abundant presence of secondary metabolite transporters, their identification, and functional characterization. A better understanding of plant secondary metabolite transporters will surely be a step forward to fulfill the steeply increasing demand for bioactive compounds for the formulation of herbal medicines. Thus, the engineering of transporters by modulating their expression is emerging as the most viable option to achieve the long-term goal of systemic metabolic engineering for enhanced metabolite production at minimum cost. In this review article, we are updating the understanding of recent advancements in the field of plant secondary metabolite transporters, particularly discovered in the past two decades. Herein, we provide notable insights about various types of fully or partially characterized transporters from ABC, MATE, PUP, and NPF families including their diverse functionalities, structural information, potential approaches for their identification, and characterization, several regulatory parameters, and their modulation. A novel perspective to the concept of “Transporter Engineering” has also been unveiled by highlighting its potential applications particularly in plant stress (biotic and abiotic) tolerance, secondary metabolite accumulation, and removal of anti-nutritional compounds, which will be of great value for the crop improvement program. The present study creates a roadmap for easy identification and a better understanding of various transporters, which can be utilized as suitable targets for transporter engineering in future research.